The demographic situation in the territory of Old Serbia including Kosovo and Western Macedonia on the eve of the Treaties of Karlowitz - Swoboda, Wincenty (Balcanica Posnaniensia. Acta et studia, 2003)
The text outlines the demographic situation in the territories of Old Serbia, including Kosovo and Western Macedonia, on the eve of the signing of the Karlovac Treaties (1699). The outline of the article was published in honour of its author, Wincenty Swoboda, who, due to his sudden death, did not manage to deliver the fully completed version of the text. The author emphasises the significant participation of Albanians in the uprisings against the Ottomans alongside the Serbs, especially in the 1690s, during the great migration of Serbs. He draws attention to the demographic changes caused by the Ottoman conquest and policy.